Management of drinking water consumption reading information via mobile application - Rochina Chisag, Angel Geovanny (2022)
The article evidences the implementation of a mobile application to manage information on the consumption of vital liquids in the homes that make up the administrative board of drinking water of the Santa Fe parish. Such a computer system allows for improving collection services and records, updating water consumption and monthly charges data, viewing the geographical location of the meters on a map, and synchronizing user information in real time. The study is an empirical investigation of a descriptive type - application with a quantitative modality. For project management and software development, the agile Scrum methodology was used, which allowed the tasks to be executed effectively together with the client's active participation. The preliminary results reveal that the processes in the transport of the information were optimized from the meter reading carried out by the company employee to its billing (delivery of receipt to the consumer), reducing response times, for which previously they were carried out by through printed cards and notebook for later typing and printing. In other similar projects, they also state that the development and use of technological tools for collecting water bills increase the benefits and efficiency for administrators and clients of an administrative board of a cantonal or regional locality.